ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KOTA SUKABUMI - lala Novikasari; Zulkarnain Zulkarnain (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2020)
Performance measurement is very important in evaluating the performance of local government officials or organizations in their efforts to provide services to the public. This study soughts to provide an overview of the financial performance of the Sukabumi City Government as a region that has won the Unqualified Audit Opinion from the BPK-RI in five consecutive years. The research was conducted using a descriptive quantitative approach. Regional financial ratios were used to measure the financial performance in question. Based on the results of the analysis and discussion, it was found that the Sukabumi City Government was quite capable of financing development or operations in the government by self-financing; PAD has always increased from year to year; Others Legal PAD has the highest contribution in contributing to overall PAD revenue; the level of dependence of the Sukabumi City Government on the source of transfer income on average was in the "MEDIUM" category; the achievement of the annual target of the Sukabumi City Government's PAD has been very effective; and the capital expenditure ratio in the Sukabumi City Government was still low below the average capital expenditure ratio in the regional government.